Manly of Wycherley and the Byronic Hero: Character Prototype and Type - Jamil, Adil (European Scientific Journal, ESJ, 2017)
The main purpose of study is to draw first a parallel between the Byronic Hero, a character type created by Lord Byron, and Manly the main character in Wycherley’s final play The Plain Dealer, and then to throw into question whether or not Manly should be added to the cited forebears of the Byronic Hero. In tracing the roots of the Byronic hero, as a type, scholars have cited a number of literary sources that Lord Byron possibly drew upon in molding his phenomenal hero, such as Satan of Milton’s Paradise Lost, Shakespeare’s Hamlet, Werther and Faust of Goethe, Faustus of Christopher Marlow, Rene the hero of Chateaubriand’s novella, the Greek Titan Prometheus, Cain from the Exodus, and Ahasuerus, the legendary wandering Jew who ridiculed Christ as he bore the cross to Calvary. Yet Byron’s debt to Wycherley especially to his character Manly is totally overlooked by scholars, despite the striking affinities, echoes, and parallels between the two characters in question. To elaborate this case, the major traits of the Byronic hero such as total independence, self-alienation and aimless wandering, stoicism, misanthropy, extremism, self-contradiction, and charisma would be carefully examined in the type and then compared to those of the prospective prototype. What would arise may thrust the idea that Manly of Wycherley should be included as one of the Byronic Hero’s forebears beside others, and it might substantiate the proposition that Manly of Wycherley is not only an early prototype but also a precursor of the Byronic hero. More likely Manly is one of the paradigms Byron drew upon in molding his hero. Manly is not, however, the sole influence on the poet, but for certain one of the many sources that influenced Byron’s creation.